The Role of Post-translational Modifications on the Energy Landscape of Huntingtin N-Terminus - Yalinca, Havva; Gehin, Charlotte Julie Caroline; Oleinikovas, Vladimiras; Lashuel, Hilal A.; Gervasio, Francesco Luigi; Pastore, Annalisa (Frontiers in Molecular Biosciences, 2019)
Huntington disease is a neurodegenerative disease characterised by a polymorphic tract of polyglutamine repeats in exon 1 of the huntingtin protein, which is thought to be responsible for protein aggregation and neuronal death. The polyglutamine tract is preceded by a 17-residue sequence that is intrinsically disordered. This region is subject to phosphorylation, acetylation and other post-translational modifications in vivo, which modulate its secondary structure, aggregation and subcellular localisation. We used Molecular Dynamics simulations with a novel Hamiltonian-replica-exchange-based enhanced sampling method, SWISH, and an optimal combination of water and protein force fields to study the effects of phosphorylation and acetylation as well as cross-talk between these modifications on the huntingtin N-terminus. The simulations, validated by circular dichroism, were used to formulate a mechanism by which the modifications influence helical conformations. Our findings have implications for understanding the structural basis underlying the effect of PTMs in the aggregation and cellular properties of huntingtin.